2022
DOI: 10.1101/2022.03.22.485345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic background and mistranslation frequency determine the impact of mistranslating tRNASerUGG

Abstract: Transfer RNA variants increase the frequency of mistranslation, the mis-incorporation of an amino acid not specified by the “standard” genetic code, to frequencies approaching 10% in yeast and bacteria. Cells cope with these variants by having multiple copies of each tRNA isodecoder and through pathways that deal with proteotoxic stress. In this study, we define the genetic interactions of the gene encoding tRNASerUGG,G26A, which mistranslates serine at proline codons. Using a collection of yeast temperature s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Intuitively, we expected a correlation between the growth impact and mistranslation frequency. Previously, we found this was the case when we varied the expression of a single mistranslating tRNA variant and measured mistranslation frequency and growth (73). However, for a set of five different tRNA Ser anticodon variants, Zimmerman et al found that there was not a simple correlation between growth and mistranslation (16).…”
Section: Factors Influencing the Impact Of The Trna Ala Variants On C...mentioning
confidence: 87%
“…Intuitively, we expected a correlation between the growth impact and mistranslation frequency. Previously, we found this was the case when we varied the expression of a single mistranslating tRNA variant and measured mistranslation frequency and growth (73). However, for a set of five different tRNA Ser anticodon variants, Zimmerman et al found that there was not a simple correlation between growth and mistranslation (16).…”
Section: Factors Influencing the Impact Of The Trna Ala Variants On C...mentioning
confidence: 87%